Definition and detection of vulnerable marine ecosystems on the high seas: problems with the "move-on" rule - Auster, P; Gjerde, K; Heupel, E; Watling, L; Grehan, A; Rogers, A (2011)
Fishing in the deep sea in areas beyond national jurisdiction has produced multiple problems related to management for conservation and sustainable use. Based on a growing concern, the United Nations has called on States to prevent significant adverse impacts to vulnerable marine ecosystems (VMEs) in the deep sea. Although Food and Agriculture Organization (FAO) guidelines for management were produced through an international consultative process, implementing criteria for designation of VMEs and recognition of such areas when encountered by fishing gear have been problematic. Here we discuss assumptions used to identify VMEs and current requirements related to unforeseen encounters with fishing gear that do not meet technological or ecological realities. A more precautionary approach is needed, given the uncertainties about the location of VMEs and their resilience, such as greatly reducing the threshold for an encounter, implementation of large-scale permanent closed areas, and prohibition of bottom-contact fishing. © 2010 International Council for the Exploration of the Sea. Published by Oxford Journals. All rights reserved.